Prevalence of Gastrointestinal Symptoms in Severe Acute Respiratory Syndrome Coronavirus 2 Infection: Results of the Prospective Controlled Multinational GI-COVID-19 Study. (9th January 2022) - Marasco, Giovanni; Cremon, Cesare; Barbaro, Maria Raffaella; Salvi, Daniele; Cacciari, Giulia; Kagramanova, Anna; Bordin, Dmitry; Drug, Vasile; Miftode, Edgidia; Fusaroli, Pietro; Mohamed, Salem Youssef; Ricci, Chiara; et al.
Abstract : INTRODUCTION: Gastrointestinal (GI) symptoms in coronavirus-19 disease (COVID-19) have been reported with great variability and without standardization. In hospitalized patients, we aimed to evaluate the prevalence of GI symptoms, factors associated with their occurrence, and variation at 1 month. METHODS: The GI-COVID-19 is a prospective, multicenter, controlled study. Patients with and without COVID-19 diagnosis were recruited at hospital admission and asked for GI symptoms at admission and after 1 month, using the validated Gastrointestinal Symptom Rating Scale questionnaire. RESULTS: The study included 2036 hospitalized patients. A total of 871 patients (575 COVID+ and 296 COVID−) were included for the primary analysis. GI symptoms occurred more frequently in patients with COVID-19 (59.7%; 343/575 patients) than in the control group (43.2%; 128/296 patients) ( P < 0.001). Patients with COVID-19 complained of higher presence or intensity of nausea, diarrhea, loose stools, and urgency as compared with controls. At a 1-month follow-up, a reduction in the presence or intensity of GI symptoms was found in COVID-19 patients with GI symptoms at hospital admission. Nausea remained increased over controls. Factors significantly associated with nausea persistence in COVID-19 were female sex, high body mass index, the presence of dyspnea, and increased C-reactive protein levels. DISCUSSION: The prevalence of GI symptoms in hospitalized patients with COVID-19 is higher than previously reported. Systemic and respiratory symptoms are often associated with GI complaints. Nausea may persist after the resolution of COVID-19 infection.